2024
DOI: 10.1172/jci176390
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological suppression of the OTUD4/CD73 proteolytic axis revives antitumor immunity against immune-suppressive breast cancers

Yueming Zhu,
Anupam Banerjee,
Ping Xie
et al.

Abstract: Despite widespread utilization of immunotherapy, treating immune-cold tumors remains a challenge. Multiomic analyses and experimental validation identified the OTUD4/CD73 proteolytic axis as a promising target in treating immune-suppressive triple negative breast cancer (TNBC). Mechanistically, deubiquitylation of CD73 by OTUD4 counteracted its ubiquitylation by TRIM21, resulting in CD73 stabilization inhibiting tumor immune responses. We further demonstrated the importance of TGF-β signaling for orchestrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Subsequent immunoprecipitation assays consistently showed CD73 interacting with OTUD4 in TNBC cells, and in situ detection techniques showed the interaction occurred within the cytosol. These findings suggest OTUD4 may drive CD73 accumulation in TNBC ( 3 ). Notably, OTUD4 overexpression heightened levels of membrane-bound CD73 in cancer cells.…”
Section: Mechanistic Insight Into Cd73 Regulationmentioning
confidence: 85%
See 4 more Smart Citations
“…Subsequent immunoprecipitation assays consistently showed CD73 interacting with OTUD4 in TNBC cells, and in situ detection techniques showed the interaction occurred within the cytosol. These findings suggest OTUD4 may drive CD73 accumulation in TNBC ( 3 ). Notably, OTUD4 overexpression heightened levels of membrane-bound CD73 in cancer cells.…”
Section: Mechanistic Insight Into Cd73 Regulationmentioning
confidence: 85%
“…By examining 1,080 TNBC samples from The Cancer Genome Atlas (TGCA) database, the authors showed improvement in patient survival among those with breast tumors exhibiting high CD8 + T cell infiltration and low levels of CD73 expression. The findings determine a notable correlation between the aberrant increase in CD73 expression and the poor prognosis of immune-cold TNBCs ( 3 ).…”
Section: Overcoming Immunosuppressive Tumor Microenvironment In Breas...mentioning
confidence: 90%
See 3 more Smart Citations